Design, synthesis, characterization and properties of magnetic nanoparticle–nanocarbon hybrids. (January 2016) - Miyako, Eijiro; Pichon, Benoit P.; Ménard-Moyon, Cécilia; Vacchi, Isabella Anna; Lefèvre, Christophe; Bégin-Colin, Sylvie; Bianco, Alberto
Abstract: Carbon nanostructured materials such as carbon nanotubes and graphene oxide are attracting much attention due to their outstanding chemical and physical properties. Metal nanoparticle-decoration can provide additional functionalities to these nanocarbons. Many chemical methods are being used for the synthesis of these metal nanoparticle-functionalized nanocarbon hybrids. On the other hand, the outstanding properties of spinelle iron oxide magnetic (MAG) nanoparticles have been efficiently used for a variety of applications such as manipulation of biomolecules and cells, cancer hyperthermia, and medical devices. Therefore, MAG nanoparticle decoration of carbon nanotubes and graphene oxide can provide promising nanohybrid materials for nanobiotechnological applications. In this work, we present a straightforward chemical route for MAG nanoparticle decoration of nanocarbon supports including carbon nanotubes and graphene oxide using in situ high-temperature decomposition method. This chemical methodology allows precisely controlling the MAG nanoparticle content, the MAG nanoparticle size leading to a uniform coating on the different carbon supports. The properties of these new hybrids have been thoroughly evaluated. Our results show that the MAG nanoparticle decoration process strongly affects the structural and magnetic characteristics of the hybrids. The combination of MAG nanoparticle and nanocarbon materials will open the door to their use in different domains including nanocomposites, wastewater treatment, sensors, biomaterials, and cancer therapy.